Implementation of Neural Network Predictive Controller for a Supersonic Separator - Nurmelissa Suraya binti Md Ridzuan, Nurmelissa Suraya (2010)
By the end of this research, it is proven that a Neural Network Predictive Controller is able to keep the system in the desired operating region and reduce the ripples on the output therefore increasing the stability of the system.